-2(-7n-8)-8n=6(n-6)

Simple and best practice solution for -2(-7n-8)-8n=6(n-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-7n-8)-8n=6(n-6) equation:


Simplifying
-2(-7n + -8) + -8n = 6(n + -6)

Reorder the terms:
-2(-8 + -7n) + -8n = 6(n + -6)
(-8 * -2 + -7n * -2) + -8n = 6(n + -6)
(16 + 14n) + -8n = 6(n + -6)

Combine like terms: 14n + -8n = 6n
16 + 6n = 6(n + -6)

Reorder the terms:
16 + 6n = 6(-6 + n)
16 + 6n = (-6 * 6 + n * 6)
16 + 6n = (-36 + 6n)

Add '-6n' to each side of the equation.
16 + 6n + -6n = -36 + 6n + -6n

Combine like terms: 6n + -6n = 0
16 + 0 = -36 + 6n + -6n
16 = -36 + 6n + -6n

Combine like terms: 6n + -6n = 0
16 = -36 + 0
16 = -36

Solving
16 = -36

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 8z+4-5z=44-5 | | 12x-2(6x-10)=1 | | g(x)=x-25x^3 | | x+36-12=42 | | 4y-12=2x | | -5(v+1)+5(1-7v)=4v+4v | | 8z+4+5z=44-5z | | -2(7n-8)-8n=6(n-6) | | -1x-7=18 | | 3(x^2+4x-1)=0 | | -20+2y=-22 | | 18+2x-12=42 | | 4(f-3)=-4 | | 2(y-1)+y=37 | | -6+14x=36 | | 10(s-6)=-129 | | 8x-24=5x+57 | | 0=x-25x^2 | | -(c-9)=-2 | | -5(5a+4)=55 | | =-x-5x-2 | | x=-16t^2+900 | | 8x-3x=1.5 | | -15+11=n-13 | | 2x+7+43=90 | | 6(6+8b)=-6(3+b) | | 7x^2+28x+7=-49 | | 10x+1=9x+5 | | 4(3c+1)+2=3(2c+2)+6 | | 13*3=39 | | 4(4p+3)=60 | | 5x+1-9=17 |

Equations solver categories